The Neural Correlates of the Abnormal Implicit Self-Esteem in Major Depressive Disorder: An Event-Related Potential Study - Jiang, Chen-guang; Lu, Heng; Zhang, Jia-zhao; Gao, Xue-zheng; Wang, Jun; Zhou, Zhen-he (Frontiers in Psychiatry, 2022)
Implicit self-esteem has been considered as a critical factor in the development and maintenance of major depressive disorder (MDD). Further investigating the ERP characteristics of the cognitive processing of the low implicit self-esteem in MDD would be helpful in understanding the neural mechanism of MDD. The purpose of this study was to investigate the neural mechanism of low implicit self-esteem in MDD. Participants included thirty-two MDD patients and thirty-one healthy controls (HCs). All participants measured with HAMD and Rosenberg Self-esteem Scale (RSES), and self-esteem Go/No-go association task (GNAT). ERPs were measured under the self-esteem GNAT. Results showed that compared to HCs, MDD patients responded less Accuracy and longer RTs in Self-Positivity condition, meanwhile MDD patients acquired the lower D scores; RSES scores in the HC group were higher than those in the MDD group. In the MDD group, the Self-Negative condition induces larger P300 amplitudes than the Self-Positive condition, and MDD patients present lower P300 amplitudes than that of HCs in the Self-Positive condition，but not in the Self-Negative condition. In the Self-Positive condition MDD patients present lower P300 amplitudes than the HC group at the middle parietal site. It concluded that MDD patients present cognitive processing dysfunctions of implicit self-esteem, and cognitive processing deficits of implicit self-esteem show abnormal ERP responses at the middle parietal cortex sites.